Wearout evaluation of mechanic parts with multimaterial 3D printing (Transactions on Additive Manufacturing Meets Medicine, 2022)
Evaluating the reliability of a part is of great importance when developing components and devices in medical engineering. In order to examine the wear on the surface of mechanical components, a thin top layer of the part is 3D printed in a different color of the same material. Thus, after performing a wear out test with the component, the mechanical wear can be visually inspected.
Keywords: Medical Engineering; Additive Manufacturing; Quality Control; Multimaterial 3D printing; Evaluation; testing; Predictive Maintenance; Mechanical Engineering; Design Evaluation